Efektivitas Terapi Musik dalam Menurunkan Ansietas pada Pasien yang Dirawat di Ruang Intensif - A N Dahlia Sinambela; Dewi Irawati; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of music therapy in reducing anxiety in patients treated in the intensive care unit. The method used is a literature review design, a scientific article literature review conducted to answer predetermined research questions. A search for articles was carried out in a structured manner in November 2022 through an online database, including using predefined keywords, namely